Sex/gender effects of glial reactivity on preclinical Alzheimer’s disease pathology - Vila-Castelar, Clara; Akinci, Muge; Palpatzis, Eleni; Aguilar-Dominguez, Pablo; Operto, Gregory; Kollmorgen, Gwendlyn; Quijano-Rubio, Clara; Blennow, Kaj; Zetterberg, Henrik; Falcon, Carles; Fauria, Karine; Gispert, Juan Domingo; et al. (Molecular psychiatry, 2025)
Glial reactivity may contribute to sex/gender differences in Alzheimer’s disease (AD) pathophysiology. Here, we investigated the differential effect of cerebrospinal fluid (CSF) glial markers on AD pathology and neurodegeneration by sex/gender among cognitively unimpaired older adults at increased risk of developing AD. We included 397 participants from the ALFA+ cohort with CSF Aβ 42/40 , p-tau 181 , sTREM2, YKL40, and GFAP, magnetic resonance imaging-based hippocampal volume (n = 299), and amyloid burden (centiloids) measured with [ 18 F] flutemetamol positron emission tomography (n = 341). We ran multiple linear regression models to assess the association between glial markers, AD pathology and hippocampal volumes and their interaction with sex/gender, using False Discovery Rate to correct for multiple comparisons. Glial markers significantly contributed to explain amyloid burden, tau pathology, and hippocampal volumes, beyond age and/or primary AD pathology in a sex/gender-specific manner. Compared to men, women showed increased amyloid burden (centiloids) and CSF p-tau 181 with increasing levels of sTREM2 and YKL40, and YKL40 and GFAP, respectively. Compared to women, men with greater tau burden showed lower hippocampal volumes as CSF YKL40 levels increased. Overall, our findings suggest that glial reactivity may contribute to sex/gender differences in AD progression, mostly, downstream amyloid. Further research identifying sex/gender-specific temporal dynamics in AD development is warranted to inform clinical trials.